International Transport, the Concept and Essence of Liability in International Freight Transportation in the Context of Supply Chain Management - Etibar Aliev (International Journal of Supply Chain Management, 2020)
Abstract— There is a number of reasons that motivate commercial enterprises to ensure supply chain sustainability. The key issues are retaining existing customers and attracting new ones; these processes are inextricably connected with the observance of international principles of sustainable business. A production-based business strives to enter the international market; as a result, this involves import and export operations, freight transportation built on contractual relationships. The study discusses the legislative regulation of the liability of participants in international freight transportation relations as a component of supply chains, as well as the problems and prospects for its development. A review and analysis of the concept of multimodal freight transportation in the context of its application have been carried out; the shortcomings of the legal regulation of this type of transportation associated with the delimitation of the scope of various international acts and jurisdictions have been considered.